2021
DOI: 10.1002/anie.202100049
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Studies of the Iron‐Catalyzed Selective and Controllable Defluorosilylation of Unactivated Aliphatic gem‐Difluoroalkenes

Abstract: The first iron-catalyzed defluorosilylation of unactivated gem-difluoroalkenes was developed, delivering gemdisilylated alkenes and (E)-silylated alkenes with excellent efficiency.T his protocol features good functional group compatibility and excellent regio-and stereoselectivity,e nabling the late-stage silylation of biologically relevant compounds,t hus providing good opportunities for applications in medicinal chemistry.Preliminary mechanistic studies and DFT calculations reveal that anucleophilic addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 91 publications
1
26
0
Order By: Relevance
“…The mechanism of iron-catalyzed silylation reaction was depicted in Scheme 3. First, the iron species was treated with silylborane reagent 2a to form an iron-boryl or iron-silyl complex I, [54][55] which was then coordinated with the nitrile to afford complex II, followed by borane insertion to form iron species III. Intermediate iron complex III then delivered iron-aryl complex IV, which reacted with silylborane reagent 2a to afford the silylated product or borylated product and regenerated iron-boryl or iron-silyl complex I.…”
Section: Scheme 2 Gram-scale Syntheses and Late-stage Functionalizati...mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of iron-catalyzed silylation reaction was depicted in Scheme 3. First, the iron species was treated with silylborane reagent 2a to form an iron-boryl or iron-silyl complex I, [54][55] which was then coordinated with the nitrile to afford complex II, followed by borane insertion to form iron species III. Intermediate iron complex III then delivered iron-aryl complex IV, which reacted with silylborane reagent 2a to afford the silylated product or borylated product and regenerated iron-boryl or iron-silyl complex I.…”
Section: Scheme 2 Gram-scale Syntheses and Late-stage Functionalizati...mentioning
confidence: 99%
“…Our recent studies revealed that iron catalysts could react with silylborane and borane reagents to generate iron-silyl and iron-boryl species, which could then promote the silylation and borylation of C-F bonds. [54][55] Inspired by these findings, [51][52][53][54][55] we envisioned that the bifunctional silylborane reagents could serve as both silicon and borane reagents in the iron catalytic system, and undergo the silylation and borylation with the aid of ligands, providing the corresponding silylated and borylated products, respectively (Scheme 1c). Herein, we report the first example of selective decyanative silylation or borylation of the same substrate using a common silylborane as either the silicon or borane reagent under iron catalysis.…”
mentioning
confidence: 99%
“…Therefore, it has been and still is widely used in many fields, from ancient but still applicable appliance as feedstock to construct basic steel tools [148], to the most recent nanotechnology field [149]. Iron presents powerful catalyst properties [150][151][152], including applications in C-H activation reactions [153][154][155].…”
Section: Iron-catalyzed C-h Activationmentioning
confidence: 99%
“…The distinction of which reaction takes place relies not only on the structure of the coupling partner, but also on the structure of the reactant itself since there are two removable hydrogen atoms necessary for the tetrasubstituted alkene to be formed (Scheme 71A and B). The method was also applied in a late-stage functionalization of bioactive molecules such as an estrone derivative (229) and donepezil (152) [219]. In both cases, the final products were successfully formed in good yields (Scheme 71C).…”
Section: Nickel-catalyzed C-h Activationmentioning
confidence: 99%
“…Usually, many unpredictable reactions are discovered by the one-electron transfer pathway, thus highlighting the superiority of iron catalysis . In our previous work, we found different reactivities of iron catalysis. Fortunately, in the recent defluorosilylation of unactivated aliphatic gem -difluoroalkenes, iron catalysis showed different reactivity from copper, palladium, and nickel.…”
mentioning
confidence: 99%